Market strategies and business models for internet-based management education: implications for knowledge management. (1st January 2003) - Enders, Albrecht; Hutzschenreuter, Thomas
The article discusses the application possibilities of the internet in the field of management education. As the importance of knowledge management efforts in companies increases, educational programs meant to broaden the knowledge base of employees are becoming more and more relevant. Today, the internet is used widely to deliver educational programs. Depending on the educational demands of different learning requirements, however, the usage of the internet varies. In the segment of continuing education programmes, it can serve to provide complete degree programs – such as an MBA – which are combined with residential modules. A higher degree of internet usage can be found in the segment of short education modules, which provide the highest degree of special and temporal flexibility and are geared towards full-time working managers. A number of examples for these program types are cited. Furthermore, the article also discusses three possible business models for offering internet-based programs: in the "integrated model", content specialists deliver all the value-creating functions by themselves; in the "packaging model", technology specialists source educational content from external suppliers, which they then package and distribute; in the "broker model", educational portals on the internet source turn-key educational products from a number of external suppliers and market and distribute these products to end customers.